Major Trauma and the use of Tranexamic Acid in Children - Javed Iqbal, Ghazala Firdous, Hafiz Muhammad Imran Aziz, Syed Faisal Usman, Muhammad Afzal, Muhammad Sharif, Fatima Naumeri, Kashif Bashir, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective was to determine reduction in blood loss in children with major trauma with or without using Tranexamic acid Methods: A study included 260 patients admitted to pediatric surgery departments at Mayo Hospital, Children's Hospital, and Jinnah Hospital in Lahore, from September, 2018 to April, 2019. Patients were divided into Tranexamic acid and control groups. Both groups received standard treatment and blood transfusion requirements. Patients were followed for length of stay and final outcomes. Results: Mean injury severity score in case and control groups was 26.61±11.17 and 29.00±11.64 respectively. Mean hospital stay was significantly shorter (p = 0.002], massive blood transfusions were significantly low [3.8% vs. 38.46%, p-value<0.001] and need of surgery [24.6% vs. 46.15%, p <0.001]. Mortality rate 1.54% vs. 7.69%, p =0.018 and discharge rate 98.64% vs. 92.31%,p = 0.018). Blood transfusion requirement and need of surgery were significant predictors for mortality in this study. Conclusion: Results of this study demonstrate that Tranexamic Acid can be effectively used to minimize blood transfusion requirement in children with major trauma. It effectively reduces the need of massive blood transfusion, minimizing mortality and shortens the hospital stay for pediatric patients. Keywords: Tranexamic acid, Effectiveness, Blood loss, Children, Trauma